Growth of single-layered two-dimensional mesoporous polymer/carbon films by self-assembly of monomicelles at the interfaces of various substrates - Fang, Yin (2015)
Single-layered two-dimensional (2D) ultrathin mesoporous polymer/carbon films are grown by self-assembly of monomicelles at the interfaces of various substrates, which is a general and common modification strategy. These unconventional 2D mesoporous films possess only a single layer of mesopores, while the size of the thin films can grow up to inch size in the plane. Free-standing transparent mesoporous carbon ultrathin films, together with the ordered mesoporous structure on the substrates of different compositions (e.g. metal oxides, carbon) and morphologies (e.g. nanocubes, nanodiscs, flexible and patterned substrates) have been obtained. This strategy not only affords controllable hierarchical porous nanostructures, but also appends the easily modified and multifunctional properties of carbon to the primary substrate. By using this method, we have fabricated Fe2O3–mesoporous carbon photoelectrochemical biosensors, which show excellent sensitivity and selectivity for glutathione.